PEMBERDAYAAN MASYARAKAT PESISIR MELALUI DIVERSIFIKASI PRODUK RUMPUT LAUT: STUDI KASUS DI DUSUN BORONGKALUKUA, SULAWESI SELATAN - Rahim, Sri Wahyuni; Yanti, Asri; Istnaeni, Zabhika Dinda; Andy Omar, Sharifuddin Bin; Tresnati, Joeharnani; Yaqin, Khusnul; Nadiarti, Nadiarti; Rukminasari, Nita; Parawansa, Basse Siang; Umar, Moh. Tauhid; Kudsiah, Hadiratul; Suwarni, Suwarni; Moka, Wilma Joanna Carolina; Putri, Amanda Pricella; Haerul, Andi (Kumawula: Jurnal Pengabdian Kepada Masyarakat, 2026)
Seaweed is one of the leading fishery commodities in the coastal areas of South Sulawesi, with high economic potential. However, its utilization is still predominantly limited to the sale of raw products, resulting in limited economic value added for local communities. This Community Service Program was conducted to promote seaweed product diversification through the development of value-added food products, namely seaweed-based noodles and nuggets. The activity was carried out on May 10, 2025, in Borongkalukua Hamlet, Borimasunggu Village, Maros Baru District, Maros Regency, involving coastal communities as the main participants. The implementation methods included educational sessions, demonstrations and hands-on processing practices, as well as product packaging training. Evaluation was conducted using pretest and posttest approaches to describe changes in participants' responses regarding their knowledge, technical understanding of processing, and motivation. The results showed an increase in the percentage of positive responses across most measured indicators. Participants' knowledge increased from 5–15% before the training to 60–80% after the training, while motivation increased from 45–65% to 75–93%. Overall, the program indicated an improvement in the community's understanding of utilizing seaweed as a value-added product and increased participants' interest in developing local resource-based economic activities. This program has the potential to support capacity strengthening among coastal communities and promote the more sustainable utilization of marine resources.Rumput laut merupakan komoditas perikanan unggulan di wilayah pesisir Sulawesi Selatan yang memiliki potensi ekonomi tinggi, namun pemanfaatannya masih didominasi oleh penjualan dalam bentuk mentah sehingga nilai tambah ekonomi yang diperoleh masyarakat masih terbatas. Kegiatan Pengabdian kepada Masyarakat ini dilaksanakan sebagai upaya mendorong diversifikasi produk rumput laut melalui pengolahan menjadi produk pangan bernilai tambah berupa mie dan nugget. Kegiatan berlangsung pada tanggal 10 Mei 2025 di Dusun Borongkalukua, Desa Borimasunggu, Kecamatan Maros Baru, Kabupaten Maros, dengan melibatkan masyarakat pesisir sebagai peserta utama. Metode pelaksanaan meliputi penyuluhan, demonstrasi dan praktik langsung pengolahan, serta pelatihan pengemasan produk. Evaluasi dilakukan menggunakan pretest dan posttest untuk menggambarkan perubahan respons peserta pada aspek pengetahuan, pemahaman teknis pengolahan, dan motivasi. Hasil kegiatan menunjukkan adanya peningkatan persentase respons positif pada sebagian besar indikator yang diukur. Pengetahuan peserta meningkat dari 5–15% sebelum pelatihan menjadi 60–80% setelah pelatihan, sedangkan motivasi meningkat dari 45–65% menjadi 75–93%. Secara umum, kegiatan ini mengindikasikan adanya peningkatan pemahaman masyarakat terhadap pemanfaatan rumput laut menjadi produk bernilai tambah serta meningkatnya ketertarikan peserta untuk mengembangkan aktivitas ekonomi berbasis sumber daya lokal. Program ini berpotensi mendukung penguatan kapasitas masyarakat pesisir dan pemanfaatan sumber daya laut secara lebih berkelanjutan.